Variasi Bahasa para Konten Kreator di Media Sosial Facebook - Wahidah, Baiq Yulia Kurnia; Putra, Agus Darma; Mahsusi, Juni (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2025)
The use of language variations for content creators is one of the choices to provide uniqueness in each content created. The choice of language is evident in several variations, including Indonesian, Sasak, code switching from Indonesian to regional languages, and the use of slang. This study aims to describe the various language variations that are the choice of content creators on Facebook social media. The method in this study is documentation and data transcription. The results of this study are to describe the languages ​​​​that are the choice of content creators on Facebook social media, as well as to describe the factors causing these language variations.